2021
DOI: 10.1186/s13765-020-00572-4
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic supplementation with prebiotic Schizophyllum commune derived β-(1,3/1,6)-glucan and probiotic concoction benefits gut microbiota and its associated metabolic activities

Abstract: Synbiotics synergistically favors beneficial effects of prebiotics and probiotics towards host metabolic health by modulating gut ecosystem. In this study, we sought to examine the effects of prebiotics (Schizophyllum commune derived β-(1,3/1,6)-glucan), probiotics (concoction made of eight different bacterial strains) and synbiotics (prebiotics + probiotics) on gut microbiota and its associated metabolic functions through 16S rRNA gene sequences analysis. Results showed that probiotics strains used in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Other than prebiotics, synbiotic treatments can also be administered to promote butyrate production in the gut ( Gurry, 2017 ). Synbiotics contain a combination of prebiotics and probiotics, and their synergistic effects are more prominent than those of prebiotics and probiotics used individually ( Singh et al, 2021 ). Synbiotic treatment with Bacillus subtilis DSM 32315 and L-Alanyl-L-glutamine improved butyrate levels and enhanced the major butyrate producers such as Faecalibacterium prausnitzii , both in vitro and in humans ( tom Dieck et al, 2022 ).…”
Section: Impact Of Selective Dietary Interventions To Enhance Butyrat...mentioning
confidence: 99%
“…Other than prebiotics, synbiotic treatments can also be administered to promote butyrate production in the gut ( Gurry, 2017 ). Synbiotics contain a combination of prebiotics and probiotics, and their synergistic effects are more prominent than those of prebiotics and probiotics used individually ( Singh et al, 2021 ). Synbiotic treatment with Bacillus subtilis DSM 32315 and L-Alanyl-L-glutamine improved butyrate levels and enhanced the major butyrate producers such as Faecalibacterium prausnitzii , both in vitro and in humans ( tom Dieck et al, 2022 ).…”
Section: Impact Of Selective Dietary Interventions To Enhance Butyrat...mentioning
confidence: 99%
“…The above has been proved with some studies like the one carried out by Singh et al , 75 who not only evaluated the effect of probiotics but also that of prebiotics and synbiotics. In this research, they found that while the probiotic modulated the microbial community, it did not increase the metabolic production of SCFAs – on the contrary, it showed depleted metabolic activity in this regard – whereas in the treatments with prebiotics and synbiotics, the metabolic activity was not depleted.…”
Section: Modulatory Effect Of Selected Biocompounds Probiotics and Pr...mentioning
confidence: 79%
“…This treatment also increased the abundance of the bacterial genera Butyricimonas and Bifidobacterium. 31 75 Supplementing the diet with probiotics will lead to an increase in the counts of probiotic microorganisms in the gut microbiota, as shown by several studies. [67][68][69][70][71] However, it is important to note that probiotics alone cannot modulate the production of microbial metabolites.…”
Section: Probiotics and Synbioticsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, arabinogalactan consists of a galactan backbone with galactose and arabinose side chains, and both SCH and Lami are β-1,3 beta-glucans with β-1,6 branching, with the degree of branching being higher in the case of SCH [ 33 ]. In addition, the molecular weight of SCH is about 1.78 × 10 6 Da) [ 34 ], which was higher than other prebiotics tested. On the other hand, these low productions of SCFAs could have been due to intrinsic limitations of the in vitro analysis, where all of the enzymatic reactions were performed in a shaker to mimic peristalsis.…”
Section: Resultsmentioning
confidence: 99%